FORMATION OF BASE COMPETENCIES RELATED TO WORD FORMATION IN PRIMARY SCHOOL STUDENTS (American Journal of Pedagogical and Educational Research, 2023)
This scientific article is devoted to the issues of technologies for the formation of competencies related to word formation among elementary school students, information is provided on the methods of word formation in the Uzbek language. The theoretical significance of the formation of competencies of elementary school students in terms of word formation, methodological recommendations and didactic tasks to achieve the goal are described.